Balancing Supercapacitor Voltages in Modular Bidirectional DC–DC Converter Circuits - Peña, Robert Alfie S. (Archīum Ateneo, 2022)
At present, passive balancing methods dominate energy storage applications, however, they suffer from a long balancing duration. In this article, we took advantage of a modular architecture, where several modular power converters replace a central dc–dc converter for fast charging and balancing of a supercapacitor stack. A strategy has been proposed to control how power is shared among the converters during the charging period in order to balance the supercapacitors. However, some converters enter control saturation due to voltage differences between supercapacitors caused by their nonuniform conditions and characteristics. The originality of this article lies in taking into account the saturation by modifying an energy-based strategy to correct the power shares and make balancing the supercapacitors possible. Simulation and experimental case studies were used to demonstrate the strategy's performance and limitations.